2014
DOI: 10.1016/j.jaapos.2014.06.016
|View full text |Cite
|
Sign up to set email alerts
|

The effects of surgical factors on postoperative astigmatism in patients enrolled in the Infant Aphakia Treatment Study (IATS)

Abstract: Purpose To evaluate the impact of surgical factors such as incision type, number of sutures, and technique of closure on postoperative astigmatism in infants undergoing cataract extraction with or without intraocular lens implantation. Methods The IATS is a multicenter (n=12) clinical trial in which 114 infants with unilateral congenital cataracts were randomized to undergo cataract extraction with intraocular lens (IOL) placement or contact lens aphakic correction. Surgical videos were reviewed with regard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…For this reason several authors concentrated their attention on how to minimize astigmatism onset after surgery, focusing their attention to the astigmatism present before 2224 and after surgery. 2529 To make such an evaluation, it is mandatory to perform a vectorial analysis. 30 However, we decided not to check this in our patients because this topic has been widely studied in the international literature, 2529,31 and we could have added no new information.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason several authors concentrated their attention on how to minimize astigmatism onset after surgery, focusing their attention to the astigmatism present before 2224 and after surgery. 2529 To make such an evaluation, it is mandatory to perform a vectorial analysis. 30 However, we decided not to check this in our patients because this topic has been widely studied in the international literature, 2529,31 and we could have added no new information.…”
Section: Discussionmentioning
confidence: 99%
“…However these studies are of older date when large corneal incisions were used. A more recent study in children undergoing unilateral surgery at age 28 days to <7 months and evaluated at 1 year of age found that corneal astigmatism regressed in aphakic children but remain unchanged in pseudophakic children 20 . Interestingly, a long‐term study of 12 pseudophakic eyes from nine children showed an increase in corneal astigmatism over time 11 .…”
Section: Discussionmentioning
confidence: 97%
“…A more recent study in children undergoing unilateral surgery at age 28 days to <7 months and evaluated at 1 year of age found that corneal astigmatism regressed in aphakic children but remain unchanged in pseudophakic children. 20 Interestingly, a long-term study of 12 pseudophakic eyes from nine children showed an increase in corneal astigmatism over time. 11 Stepwise regression analysis did show a higher level of astigmatism on the back of the cornea associated to pseudophakia but no association between pseudophakia and the level of astigmatism on the front of the cornea was found.…”
Section: Discussionmentioning
confidence: 98%
“… 18 , 19 , 20 , 22 , 23 , 28 , 29 The results of the studies indicated that CL wear is more advantageous in infancy, IOL implantation is safer after 2 years of age, and secondary IOL surgery at later ages will result in less refractive error. 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 …”
Section: Introductionmentioning
confidence: 99%